ANALISIS PENGENDALIAN DAYA REAKTOR PCMSR DENGAN PENGATURAN LAJU ALIR PENDINGIN - Noha, Iqbal Syafin; Widiharto, Andang; Sihana (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2013)
Passive Compact Molten Salt Reactor (PCMSR) is the development of Molten Salt Reactor (MSR) which has different character from other five generation IV reactors, it uses molten salt as fuel. In MSR, the molten salt is not used as coolant but it is used as fuel medium carrier. Due to fuel phase in the form of molten salt of LiF-BeF2-ThF4-UF4, then the power control can be done by controlling fuel and coolant flow rate. The goal of this study is to know the effect coolant flow rate change toward PCMSR power. The analysis examined four kinds of coolant flow rate change input, those are step, ramp, exponential, and sinusoidal input. For the step input, the coolant flow rate was changed suddenly. For the ramp input, the flow rate was changed linearly. In the exponential input, the flow rate is increased and decayed following exponential function. In the sinusoidal input, the flow rate experienced fluctuate change periodically by frequency variation of the flow rate. The result of the study showed that 50% of coolant flow rate decreasing causes 63% of PCMSR power decreasing from the previous power. If a fluctuate change occur in the coolant flow rate, the higher fluctuate change (frequency) of the coolant flow rate, the less power response given. At a very fast frequency, the reactor power becomes constant and tends not to respond the flow rate. The the one of the reactor safety aspect due to the reactor will not response very fast changes. The ability of the reactor to ajust its power follow the coolant flow rate is the other safety aspect.